1985
DOI: 10.1111/j.1365-2133.1985.tb02336.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of accentuated palmoplantar markings and keratosis pilaris in atopic dermatitis, autosomal dominant ichthyosis and control dermatological patients

Abstract: The prevalence of keratosis pilaris and accentuated palmoplantar marking was evaluated in 61 patients with atopic dermatitis, 35 patients with dominant ichthyosis vulgaris and 247 other dermatological cases taken as controls. Our data showed that (1) these features are of no diagnostic significance for atopic dermatitis and (2) they are significantly more frequent in patients with ichthyosis vulgaris without associated eczema than in those with atopic dermatitis. Consequently, they should be considered as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 12 publications
4
45
0
3
Order By: Relevance
“…1 -4 Individuals with IV are characterized by a life-long history of generalized fine scaling that is accentuated on the extensor surfaces of the extremities and typically spares the great flexures and the neck. Associated findings include hyperkeratosis and hyperlinearity of the palms ('I-hand') and soles, 5 keratosis pilaris, 6 hypohydrosis, 7 atopic dermatitis (AD), 8 allergic rhinoconjunctivitis and asthma. 7,9 Histologically, the epidermis of IV subjects is characterized by hyperkeratosis and an attenuation or absence of the granular layer; 10 -12 however, in approximately 25 -50% of patients diagnosed with IV based on clinical criteria the stratum granulosum is histologically normal.…”
Section: Introductionmentioning
confidence: 99%
“…1 -4 Individuals with IV are characterized by a life-long history of generalized fine scaling that is accentuated on the extensor surfaces of the extremities and typically spares the great flexures and the neck. Associated findings include hyperkeratosis and hyperlinearity of the palms ('I-hand') and soles, 5 keratosis pilaris, 6 hypohydrosis, 7 atopic dermatitis (AD), 8 allergic rhinoconjunctivitis and asthma. 7,9 Histologically, the epidermis of IV subjects is characterized by hyperkeratosis and an attenuation or absence of the granular layer; 10 -12 however, in approximately 25 -50% of patients diagnosed with IV based on clinical criteria the stratum granulosum is histologically normal.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually aggravated in the winter time [5]. It has been associated with ichthyosis vulgaris and atopic dermatitis [3, 5]. In a previous study of young patients with insulin-dependent diabetes mellitus (IDDM) we found that the prevalence of KP was higher than in healthy controls, with a high correlation with high body mass index (BMI) and ichthyosiform skin changes on the shins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence as found in different studies ranges from 2% in Brazil to 44% in Switzerland and is as high as 80% in adolescent girls in England [2, 3, 4]. It appears in childhood, reaching its peak incidence in adolescence, and is more prevalent in girls [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] IV, the most prevalent disorder of cornification in humans, is characterized by the delayed, postnatal onset of generalized, fine scaling that spares the flexures, and is often associated with palmar hyperlinearity and atopic dermatitis (AD). [5][6][7] In IV and AD, both nonsense and frameshift mutations have been discovered in the gene encoding FLG, which localizes to the epidermal differentiation complex on chromosome 1q21. 8 -17 Phenotype severity appears to be subject to a dose effect, wherein heterozygous patients show a milder phenotype with reduced, but not absent, FLG, whereas IV patients with homozygous or compound heterozygous FLG mutations typically lack FLG and exhibit a more severe scaling phenotype with a greater predisposition for early development and more severe AD.…”
mentioning
confidence: 99%